Role of MafB in macrophages - Hamada, Michito (Exp Anim, 2019)
The transcription factor MafB regulates macrophage differentiation. However, studies on the phenotype of Mafb-deficient macrophages are still limited. Recently, it was shown that the specific expression of MafB permits macrophages to be distinguished from dendritic cells. In addition, MafB has been reported to be involved in various diseases related to macrophages. Studies using macrophage-specific Mafb-deficient mice show that MafB is linked to atherosclerosis, autoimmunity, obesity, and ischemic stroke, all of which exhibit macrophage abnormality. Therefore, MafB is hypothesized to be indispensable for the regulation of macrophages to maintain systemic homeostasis and may serve as an innovative target for treating macrophage-related diseases.